Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Trouve-Toi Une Job ! : Petite Histoire Des Luttes Pour Le Droit À L'assurance-Chômage - Mouvement Action-Chômage Montréal (Écosociété, 2022)
Keywords: Chômage; Groupes populaire

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

Construire une citoyenneté urbaine par le droit de vote au municipal: lois électorales et contestations militantes à Montréal de 1965 à 1974 - Robert, Vincent (Université de Montréal, 2022)
Keywords: Femmes; Libéralisme; Montreal Local Council of Women; Rassemblement des citoyens et citoyennes de Montréal; Élections

L'intendance sociale du capital : philanthropie d'entreprise et hôpitaux généraux montréalais, 1880-1915 - Dubreuil, Anne-Marie (Université du Québec à Montréal, 2022)
Keywords: Hôpital Notre-Dame; Hôpitaux; Montreal General Hospital; Philanthropie; Royal Victoria Hospital

Le Montréal juif – (3e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

« Nous ne parlerons pas de la guerre » : la participation oubliée de l’Université de Montréal à la Seconde Guerre mondiale - Walling, Jeremy John (Cahiers d'histoire, 2022)
Keywords: Guerre; Quartier latin (Le); Université de Montréal; Étudiants

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

Travailleuses anonymes et modernité énergétique. L’industrie électrique et gazière et l’économie domestique à Montréal, 1904-1959 - Hatton-Proulx, Clarence (Revue d'histoire de l'Amérique française, 2022)
Keywords: Femmes; Montreal Light, Heat and Power; Travail; École ménagère; Électricité

Le Montreal Local Council of Women et la Fédération nationale Saint-Jean-Baptiste: Entre identités et marginalisations, 1893-1914. - Béliveau, Geneviève (Consommation et identité: production et occupation de l’espace aux XIXe et XXe siècles. Actes des 25e et 26e colloques étudiants du CIEQ, 2022)
Keywords: Bourgeoisie; Femmes; Fédération nationale Saint-Jean-Baptiste; Montreal Local Council of Women

Histoire du Conseil régional FTQ Montréal métropolitain. Les années 1986-2021: Entre persévérance et renouvellement - Bédard, Caroline; Busic, Milan (Service aux collectivités de l'Université du Québec à Montréal, Conseil régional FTQ Montréal, 2022)
Keywords: Fédération des travailleurs et des travailleuses du Québec (FTQ); Grèves; Travail

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Femmes et cinéma d'animation: un corpus féministe à l'Office national du film du Canada (1939-1989) - Saint-Pierre, Marie-Josée (PUM, 2022)
Keywords: Cinéma; Femmes; Féminisme; Office national du film

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Les Pharmacies Leduc, 100 ans d'existence - Leduc, Guy (Il était une fois...Montréal-Nord, 2022)
Keywords: Pharmacie

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

''L’autisme, cet inconnu'' : représentations expertes et populaires du trouble du spectre de l’autisme dans les quotidiens montréalais de 1970 à 1998 - El-Sabbagh, Marianne (Université de Montréal, 2022)
Keywords: Devoir (Le); Presse (La)

Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

Histoire de la biomédecine au Québec : la physiologie cardio-respiratoire à l'Institut Lavoisier de Montréal (1950-1956) - Ouimet, Benoit (Université du Québec à Montréal, 2022)

Former et être formée au travail domestique : l'enseignement ménager et la couture à l'école publique québécoise (1937-1969) - Brisebois, Marilyne (Université Laval, 2022)
Keywords: Commission des écoles catholiques de Montréal; Femmes; Étudiants

Le Québec anglophone: une communauté distincte du reste du Canada? : étude comparative des positions éditoriales de deux journaux anglophones - The Gazette et The Globe and Mail - en rapport avec certains débats publics au Québec et au Canada de 1976 à 1982 - Lacasse, Chantal (Université Laval, 2022)
Keywords: Anglophones; Francophones; Fédéralisme; Indépendantisme; Montreal Gazette; Nationalisme

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

Le Comité d’Habitation de Montréal - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Groupes populaires; Logement

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

‘We have always been here’: Busking, urban space and economy of Montreal - Chatterjee, Piyusha (Université Concordia, 2022)

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

Sir Hormisdas Laporte: Homme d'affaires et maire de Montréal (1850-1934) - Saint-Pierre, Marjolaine (Septentrion, 2022)
Keywords: Maires; Philanthropie

“A Curse or a Blessing?”: Montreal Jews and the Politics of 1960s Quebec - Lacasse, Simon-Pierre (Canadian Historical Review, 2022)
Keywords: Juifs; Nationalisme

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Les ateliers d’histoire, issus de l’action citoyenne au coeur des quartiers montréalais - Carbonneau, Réjean (Cap-aux-Diamants, 2022)
Keywords: Atelier d'histoire d'Hochelaga-Maisonneuve; Histoire

Le travail traditionnel dans les carrières de calcaire de Montréal: un prélude à la carrière Rhéaume - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Artisans; Carrière; Charretiers; Travail

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Choléra; Épidémies

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

La Maison d’Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972–1986 - Rochat, Désirée (Histoire sociale / Social History, 2022)
Keywords: Haïtiens; Noirs

Histoire et pratique d’érudition au XIXe siècle. Le cas de la Numismatic and Antiquarian Society of Montreal - Vaudry-L., Flavie (Cap-aux-Diamants, 2022)
Keywords: Numismatie

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Logement

Looking Around: The Architecture of Medical Education - Adams, Annmarie (Transforming Medical Education: Historical Case Studies of Teaching, Learning, and Belonging in Medicine, 2022)
Keywords: Médecine; Université McGill

Red mitten nationalism: sport, commercialism, and settler colonialism in Canada - Fresco, Estée (McGill-Queen's University Press, 2022)
Keywords: Autochtones; Jeux olympiques; Nationalisme

Faire mouvement: les quarante ans du Mouvement d'éducation populaire et d'action communautaire du Québec - Collectif Faire Mouvement (Rue Dorion, 2022)
Keywords: Groupes populaire

« Il y a plus de crime à détruire un enfant, qu'à le faire » : traitement communautaire et judiciaire de l'infanticide en Nouvelle-France (1671-1747) - Chasle, Ariane (Université de Montréal, 2022)
Keywords: Criminalité; Enfants; Tribunaux

It Was a Man's World: Blaine Baker and the Writing of Canadian Legal History, 1981-2018 - Young, Brian (Law, Life, and the Teaching of Legal History. Essays in Honour of G. Blaine Bake, 2022)
Keywords: Ensiegnants; Histoire; Historiens; Université McGill